Implementation of Sustainable Finance Taxonomy Policy through Sustainable Credit: Regulations, Opportunities, and Challenges for Banks in Indonesia - Novianto, Muhammad Rifqi; Abubakar, Lastuti; Handayani, Tri (Dinasti Research, 2025)
Indonesia's commitment to the Sustainable Development Goals (SDGs) and the Paris Agreement has implications for banks in carrying out their business practices to lead to sustainable practices. The phenomenon occurs when banks indirectly contribute to causing environmental damage such as providing credit that is only oriented towards profit. The Financial Services Authority (OJK) as a regulator issues the Sustainable Finance Taxonomy Policy as a guideline for banks to maximize the implementation of sustainable finance, especially in providing credit. This study aims to analyze how the Sustainable Finance Taxonomy policy influences and plays a strategic role in increasing sustainable banking credit in Indonesia. This study uses a normative legal approach with analytical descriptive specifications and the object of research is PT Bank Mandiri (Persero) Tbk, this study found that the Sustainable Finance Taxonomy policy plays a strategic role in increasing sustainable credit. The results of this study are expected to provide knowledge for policy makers in creating a sustainable financial system with legal certainty.